2011
DOI: 10.1249/mss.0b013e318205e2d6
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Talking Pedometer for Adults with Visual Impairment

Abstract: In unfamiliar and familiar walking conditions, the Centrios pedometer accurately monitors step-based activity in adults with VI when mounted at the hip opposite the user's MA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…As the prevalence of morbidity continues to proliferate in all populations, establishing time frame recommendations and variance estimates pertaining to physical activity assessment seems a necessary and useful step in developing and implementing health-related interventions. In particular, among persons with VI, the availability of adapted pedometers (Holbrook et al, 2011) and accurate knowledge of the appropriate physical activity monitoring time frame makes the delivery of an effective, population-specific health intervention more feasible. As with all studies, however, this investigation is not without limitations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As the prevalence of morbidity continues to proliferate in all populations, establishing time frame recommendations and variance estimates pertaining to physical activity assessment seems a necessary and useful step in developing and implementing health-related interventions. In particular, among persons with VI, the availability of adapted pedometers (Holbrook et al, 2011) and accurate knowledge of the appropriate physical activity monitoring time frame makes the delivery of an effective, population-specific health intervention more feasible. As with all studies, however, this investigation is not without limitations.…”
Section: Discussionmentioning
confidence: 99%
“…While the voice-announcement technology contained within the device makes the Centrios pedometer larger than typical spring-levered monitors, automated feedback can be announced at the touch of a button or periodically throughout the day (e.g., after every 1,000 steps or 10 min of accumulated activity time). When worn by adults with VI, the Centrios pedometer provides estimates of step-based physical activity with an acceptable degree of accuracy (< 2.7% of actual steps) when mounted at the hip opposite the user's mobility aid (Holbrook et al, 2011).…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Daily step activity was monitored using a Centrios talking pedometer, a springlevered device with demonstrated validity (Ͻ 3% error) when worn by individuals with visual impairments employing various types of mobility devices (such as a long cane or dog guide) or no mobility devices (Holbrook, Stevens, Kang, & Morgan, 2011). This pedometer has a talking feature that allows data to be accessed audibly, and raised buttons that tactilely guide users in scrolling through various descriptors of physical activity (for instance, steps taken, caloric expenditure, and activity time).…”
Section: Physical Activitymentioning
confidence: 99%
“…Data analysis revealed that the pedometers examined-Centrios Digital Talking Pedometer (hereafter, Centrios) (Orbyx Electronics, Walnut, CA) and Digiwalker SW200 (HRM USA, Warminster, PA)-were valid, although the Centrios slightly overestimated step counts (Haegele & Porretta, 2015b). An earlier study of Centrios established validity of the pedometer when mounted on the hip opposite the user's mobility device such as a cane (Holbrook, Stevens, Kang, & Morgan, 2011). Finally, a study by Lieberman, Stuart, Hand, and Robinson (2006) revealed motivational aspects of wearing the pedometers, such as achievement of specific activity goals, a better understanding of the relation between their daily steps and their individual health and fitness, a sense of greater independence with walking, and the use of walking as a mode of independent transportation.…”
mentioning
confidence: 97%